Development Strategy for Increasing the Revenue of J-Walk Medan Entrepreneurs - Syahriany, Indha; Sirojuzilam; Erlina (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Development aims to improve and increase the welfare of the public and create innovation in the community. A A business has an important role in the economy. Because it can absorb labor, in addition, it takes the ability to understand all the needs and desires of consumers to generate higher incomes. The study aims: 1) to determine and analyze what strategies can be done in the development of J-Walk so that the revenue of entrepreneurs in J-Walk Medan increase, 2) to determine and analyze whether the factors of product, price, place and promotion affect the purchase interest of J-Walk Medan consumers. The research is carried out at J-walk Medan which is located in the residential area of J-City, Medan, precisely in the Medan Johor area. the results demonstrate that: 1) Product has positive and significant effect on purchase interest. 2) Place is not significant to purchase interest. 3) Price has a positive and significant effect on purchase interest. 4) Promotion has a positive and significant effect on purchase interest